Lead poisoning of a child associated with use of a Cambodian amulet --- New York City, 2009. (MMWR: Morbidity & Mortality Weekly Report, 2011)
Lead poisoning in children is a preventable public health problem that can adversely affect the developing nervous system and result in learning and behavior problems. The most common source of exposure for lead-poisoned children aged <6 years in the United States is lead-based paint. However, nonpaint sources have been identified increasingly as the cause of lead poisoning, particularly in immigrant communities. This report describes a case of lead poisoning in a child aged 1 year that was investigated by the New York City Department of Health and Mental Hygiene's (NYC DOHMH) Lead Poisoning Prevention Program in 2009. The likely source of exposure was an amulet made in Cambodia with leaded beads that was worn by the child. Health-care providers and public health workers should consider traditional customs when seeking sources of lead exposure in Southeast Asian populations. Health-care providers should ask parents about their use of amulets, especially those in Southeast Asian families and those with children found to have elevated blood lead levels (BLLs). Educational efforts are needed to inform Southeast Asian immigrants that amulets can be a source of lead poisoning.